2014
DOI: 10.1124/dmd.113.055996
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Nonalcoholic Steatohepatitis-Associated Changes in Drug Transporter Expression Using Experimental Rodent Models

Abstract: Nonalcoholic fatty liver disease is a prevalent form of chronic liver disease that can progress to the more advanced stage of nonalcoholic steatohepatitis (NASH). NASH has been shown to alter drug transporter regulation and may have implications in the development of adverse drug reactions. Several experimental rodent models have been proposed for the study of NASH, but no single model fully recapitulates all aspects of the human disease. The purpose of the current study was to determine which experimental NAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 44 publications
12
81
0
Order By: Relevance
“…1). Rats that received the 8-week MCD diet exhibited NASH hallmarks, including steatosis, inflammation, and fibrosis, consistent with previous reports wherein this model was scored by a trained pathologist using a validated NASH scoring system (Kleiner et al, 2005;Canet et al, 2014) and identified as histologically similar to human NASH (George et al, 2003). The effect of NASH on morphine and M3G disposition after intravenous administration of morphine was examined over 150 minutes.…”
Section: Resultssupporting
confidence: 57%
“…1). Rats that received the 8-week MCD diet exhibited NASH hallmarks, including steatosis, inflammation, and fibrosis, consistent with previous reports wherein this model was scored by a trained pathologist using a validated NASH scoring system (Kleiner et al, 2005;Canet et al, 2014) and identified as histologically similar to human NASH (George et al, 2003). The effect of NASH on morphine and M3G disposition after intravenous administration of morphine was examined over 150 minutes.…”
Section: Resultssupporting
confidence: 57%
“…It is proposed that Mrp2 induction in the kidneys may serve as an alternative route of elimination of bile acids in situations in which liver function is compromised (Klaassen and Aleksunes, 2010). Similar to cholestasis, hepatic Mrp2 function is significantly reduced in NASH whereas Mrp4 is induced, leading to a functional shift in the disposition of xenobiotics from bile to plasma Canet et al, 2014). The similarity in the changes to hepatic and renal transporter gene expression between cholestasis and NASH is suggestive of a common mechanism mediating these effects.…”
Section: Tubular Degenerationmentioning
confidence: 84%
“…Indeed, NASH causes extensive alterations in the regulation of hepatic xenobiotic transporters of both human and rodent models, leading to the functional disruption of acetaminophen, ezetimibe, methotrexate, and arsenic disposition (Lickteig et al, 2007;Hardwick et al, 2011Hardwick et al, , 2012Canet et al, 2012Canet et al, , 2014. A common observation in these studies is increased plasma retention coupled with decreased biliary elimination of xenobiotics, suggesting that patients with NASH may represent a unique population of individuals that are at higher risk of experiencing adverse drug reactions.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations